IMPLEMENTASI SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN EFEKTIVITAS PEMBAYARAN JAMINAN KESEHATAN NASIONAL DI RSU. KARYA DHARMA HUSADA - I GUSTI AYU AGUNG SRI PARTINI; GEDE WIDIASTINA (ARTHA SATYA DHARMA, 2025)
This study analyzes the implementation of an Accounting Information System (AIS) in improving the effectiveness of National Health Insurance (JKN) payments at Karya Dharma Husada General Hospital. Using a descriptive and comparative method during the period of January–March 2025, data were collected through interviews, observations, and documentation. The results show that the implementation of AIS has accelerated claim disbursement (from 30–45 days to 10–15 days), increased claim accuracy (from 70% to 95%), and reduced uncollectible receivables. In addition, AIS supports transparency, accountability, data-driven decision-making, as well as efficiency in budget planning and cost control. These findings confirm that automation and data integration through AIS not only speed up administrative processes but also strengthen operational efficiency and the hospital’s financial sustainability.